2014
DOI: 10.1007/s11064-014-1503-z
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ICA69 Potentiates Long-Lasting Hyperalgesia After Subcutaneous Formalin Injection into the Mouse Hindpaw

Abstract: Islet-cell autoantigen 69 kDa (ICA69) plays an important role in many diseases and physiological activities by forming heteromeric complexes with protein interacts with C-kinase 1 (PICK1). PICK1 is critical for inflammatory pain hypersensitivity by regulating trafficking of AMPA receptor subunit GluA2 in spinal neurons. However, the role of ICA69 in inflammatory pain has not yet been investigated. Here we reported that expression of PICK1 in spinal cord was reduced largely in ICA69 knockout mice. The pain hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…We confirmed that the GluR2-p level significantly increased after CFA injection compared with the Sham group in both ICA69-WT (WT-Sham vs WT-CFA, P < 0.001) and ICA69-KO mice (KO-Sham vs KO-CFA, P < 0.001). Furthermore, the GluR2-p level of the KO-CFA group was significantly increased compared with WT-CFA group ( P = 0.005), which supported that ICA69 KO leads to an increase of GluR2-p. 23 Electroacupuncture reduced the GluR2-p level to the baseline level in WT mice after CFA (WT-CFA vs WT-CFA+EA, P < 0.001), which was related to the analgesic effects confirmed by relevant studies. Electroacupuncture significantly downregulated GluR2-p expression in WT mice but not in ICA69-KO mice (KO-CFA+EA vs WT-CFA+EA, P < 0.001) (Figs.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…We confirmed that the GluR2-p level significantly increased after CFA injection compared with the Sham group in both ICA69-WT (WT-Sham vs WT-CFA, P < 0.001) and ICA69-KO mice (KO-Sham vs KO-CFA, P < 0.001). Furthermore, the GluR2-p level of the KO-CFA group was significantly increased compared with WT-CFA group ( P = 0.005), which supported that ICA69 KO leads to an increase of GluR2-p. 23 Electroacupuncture reduced the GluR2-p level to the baseline level in WT mice after CFA (WT-CFA vs WT-CFA+EA, P < 0.001), which was related to the analgesic effects confirmed by relevant studies. Electroacupuncture significantly downregulated GluR2-p expression in WT mice but not in ICA69-KO mice (KO-CFA+EA vs WT-CFA+EA, P < 0.001) (Figs.…”
Section: Resultsmentioning
confidence: 67%
“…ICA69-KO mice show normal spontaneous motor activity compared with their WT littermates (ICA69-WT mice). 23 We performed CFA injection with or without EA treatment on ICA69-KO mice and their WT littermates. There was no significant difference in PWF ( P = 0.195) and PWL ( P = 0.408) between the KO-Sham group and WT-Sham group, indicating that ICA69 KO did not affect the baseline of the plantar pain threshold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty minutes after drug treatment, acute inflammatory pain was induced by subcutaneous injection of 50 µl of 5% formaldehyde into the hind paw dorsum as described by Snijdelaar et al and our previous reports (24,25). This produced a typical flinching and biting response comprising 2 phases: an initial quiescent phase 1 and a prolonged tonic phase 2 beginning about 10 minutes after injection.…”
Section: Drug Treatment In Model Of Acute Inflammatory Painmentioning
confidence: 99%